2004
DOI: 10.1007/s00280-004-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of an oral formulation of irinotecan administered daily for 14�days every 3�weeks in patients with advanced solid tumours

Abstract: A phase I study was conducted with oral irinotecan given daily for 14 days every 3 weeks in 45 patients with solid tumours to establish the maximum tolerated dose (MTD), toxicity, preliminary antitumour response and pharmacokinetics. Irinotecan was administered orally as a powder-filled capsule at doses ranging from 7.5 to 40 mg/m2 per day. Tumours were predominantly colorectal (30) together with 10 other gastrointestinal, 2 breast, 2 small cell lung and 1 ovarian. All but three patients had received prior che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In our previous study, the advised future dose was 30 mg/m 2 /d for 14 days every 3 weeks (1). This was also found earlier by Sharma et al (1,35,36). In both studies, the most commonly observed DLT was diarrhea.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In our previous study, the advised future dose was 30 mg/m 2 /d for 14 days every 3 weeks (1). This was also found earlier by Sharma et al (1,35,36). In both studies, the most commonly observed DLT was diarrhea.…”
supporting
confidence: 74%
“…The appropriate daily dose of irinotecan capsules was based on the actual calculated body surface area. The starting dose as a single agent was based on a previous study (1), in which powder-filled capsules were used. In part II of the study, irinotecan was administered as in part I, orally, once daily with capecitabine, orally twice daily at the end of a meal (breakfast and dinner) from days 1 to 14 every 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an oral formulation of irinotecan has been developed and has entered phase I clinical trials (Schoemaker et al, 2002). Since chronic infusions are cumbersome and expensive, an oral formulation provides an excellent method to administer irinotecan over a prolonged period at low doses.…”
Section: Gastrointestinal Originmentioning
confidence: 99%
“…infusion and is converted to its active metabolite SN-38 by carboxylesterase [24]. Oral irinotecan has unpredictable bioavailability, but some form of oral agent would have practical advantages, especially if used with an oral fluoropyrimidine [24][25][26][27][28]. No interaction between oral irinotecan and capecitabine was observed in a pharmacokinetic study [28].…”
Section: Dna Topoisomerase Inhibitionmentioning
confidence: 99%